Management System Fertilizer Ship Arrival At UPP Semarang Based Website Using Sequential Searching Algorithm - Susanto Susanto; Alda Hani Meidina (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2021)
The technical improvements of the present era necessitate that everyone understand information and communication technology. The influence can be useful in a range of industries, especially in the workplace. The office management system is a sort of administrative activity aimed at increasing management effectiveness. As a result, data management at PT. Dwimatama Multikarsa Semarang continues to be done manually, particularly in the production department, with data being input into Microsoft Excel software and stored on hard drives or flash drives. In this case, it is ineffective, especially if the data has been lost or corrupted. The author has come up with the idea of computerizing the administration and archiving system in light of the limitations that have been stated. The author uses a sequential searching approach to do a data search. This method will allow users to find information more quickly and effectively. The system was built using the Laravel framework and the Hypertext Preprocessor (PHP) programming language. The study's conclusion is a web-based data management and storage system that uses MySQL databases. Employees can benefit from this technology by being able to handle and save information more effectively and efficiently.